2017
DOI: 10.1177/1474515116687178
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ attitudes toward family importance in heart failure care

Abstract: Background: Support from the family positively affects self-management, patient outcomes and the incidence of hospitalizations among patients with heart failure (HF). To involve family members in HF care is thus valuable for the patients. Registered nurses (RNs) frequently meet family members to patients with HF and the quality of these encounters are likely to be influenced by the attitudes RNs hold toward families. Aims: To explore RNs' attitudes toward the importance of families' involvement in HF nursing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
54
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(85 citation statements)
references
References 36 publications
(113 reference statements)
16
54
2
5
Order By: Relevance
“…Most of the participating nurses indicated that they gained a lot of valuable knowledge from families, and most of them considered family members as cooperating partners. This is in line with other studies, which found that nurses are supportive of families' involvement and view families as important in care (Gusdal et al, ; Luttik et al, ). Even though nurses considered family members as cooperating partners, only half of the nurses in our study encouraged families to use their own resources.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Most of the participating nurses indicated that they gained a lot of valuable knowledge from families, and most of them considered family members as cooperating partners. This is in line with other studies, which found that nurses are supportive of families' involvement and view families as important in care (Gusdal et al, ; Luttik et al, ). Even though nurses considered family members as cooperating partners, only half of the nurses in our study encouraged families to use their own resources.…”
Section: Discussionsupporting
confidence: 92%
“…(Wright & Bell, ). Nurses attitudes towards involving families in nursing care has been explored in different clinical settings such as paediatrics (Angelo et al, ), obstetric care (Ribeiro, Sousa, Santos, Silva, & Sousa, ), primary health care (Oliveira et al, ), mental health care (Hsiao & Tsai, ), among nurses caring for patients with psychiatric diagnoses (Sveinbjarnardottir, Svavarsdottir, & Saveman, ), in cardiovascular care (Gusdal, Josefsson, Thors Adolfsson, & Martin, ; Luttik et al, ), in surgical units (Blondal et al, ) emergency departments (Linnarsson, Benzein, & Arestedt, ), in critical care units (Hetland, Hickman, McAndrew, & Daly, ; Hetland, McAndrew, Perazzo, & Hickman, ) and among home care nurses and hospital‐employed nurses (Broekema, Luttik, Steggerda, Paans, & Roodbol, ). Generally, the studies found that nurses hold positive attitudes towards family involvement in care (Hsiao & Tsai, ; Linnarsson et al, ; Oliveira et al, ), even without special training in approaches to family inclusion (Ribeiro et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 19 studies were included in this systematic review reporting on the following five instruments used to assess nurses’ attitudes towards the importance of involving families in their clinical practice: Families’ Importance in Nursing Care: Nurses’ Attitudes (FINC‐NA) (Benzein, Johansson, Arestedt, Berg, Johansson, Arestedt, Berg, & Saveman, ; Blöndal et al, ; Hsiao & Tsai, ; Luttik et al, ; Pascual Fernández et al, ) and three further versions of the scale: a revised version (FINC‐NA‐R) (Gusdal, Josefsson, Thors Adolfsson, & Martin, ; Linnarsson, Benzein, & Årestedt, ; Saveman, Benzein, Engström, & Årestedt, ), a short version (FINC‐NA‐S) (Mackie, Marshall, Mitchell, & Ireland, ) and a modified Portuguese version (IFCE‐AE) (Oliveira et al., ). Family Nurse Practice Scale (FNPS) (Hsiao & Tsai, ; Simpson & Tarrant, ). Family Nurse Caring Belief Scale (FNCBS) (Meiers, Tomlinson, & Peden‐McAlpin, ). Family‐Centered Care Questionnaire (FCCQ) (Bruce & Ritchie, ) and a revised version (FCCQ‐R) (Alabdulaziz, Moss, & Copnell, ; Bruce et al, ; Caty, Larocque, & Koren, ; Coyne, Murphy, Costello, O'Neill, & Donnellan, ). Measure of Beliefs about Participation in Family‐Centered Service (MBP‐FCS) (Asai, ; King et al, ). …”
Section: Resultsmentioning
confidence: 99%
“…1. Families' Importance in Nursing Care: Nurses' Attitudes (FINC-NA) (Benzein, Johansson, Arestedt, Berg, Johansson, Arestedt, Berg, & Saveman, 2008;Blöndal et al, 2014;Hsiao & Tsai, 2015;Luttik et al, 2017;Pascual Fernández et al, 2015) and three further versions of the scale: a revised version (FINC-NA-R) (Gusdal, Josefsson, Thors Adolfsson, & Martin, 2017;Linnarsson, Benzein, & Årestedt, 2015;Saveman, Benzein, Engström, & Årestedt, 2011), a short version (FINC-NA-S) (Mackie, Marshall, Mitchell, & Ireland, 2017) and a modified Portuguese version (IFCE-AE) (Oliveira et al., 2011). (Hsiao & Tsai, 2015;Simpson & Tarrant, 2006).…”
Section: Re Sultsmentioning
confidence: 99%